Efektivitas Pemberian Kurma Ajwa dan Sukari Dalam Meningkatkan Kadar Gula Darah Sesudah Puasa - Ahmad Said Fadillah; Rachmat Faisal Syamsu; Asrini Safitri (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
Blood sugar or known as blood glucose is the main nutritional element used for the metabolism of glucose cells in the body. Some of the effects of people who fast can be seen such as feeling weak, tired and tired. So to restore energy to people who are fasting, food is needed that can restore stamina, such as dates. In this study, we will look at the presentation of the increase or effectiveness of a person's blood sugar levels after breaking the fast by consuming Ajwa and Sukari dates. Research Objectives: This study aims to determine fasting blood sugar levels after consuming Ajwa dates and Sukari dates. Research Method: The type of research used by researchers is quantitative research. With an experimental research design on fasting blood sugar levels at Booarding School MTQ Syafi’i Makassar which was given ajwa and sukari dates. The sample management used was a one group pre test-post design by looking at the comparison of fasting blood sugar levels after consuming dates and before consuming dates. With a population of 20 people and this population was taken using a total sampling technique, carried out in August 2022. Results: It can be concluded from the results of the research I conducted that the fasting blood sugar level before consuming Ajwa dates was 96,750 ± 8.4 and after consuming Ajwa dates 147,850 ± 9.85, Fasting blood sugar levels before consuming Sukari dates were 92.85 ± 7.5 and after consuming dates 152.2 ± 7.12.